KONFLIK MANAJEMEN ANTARA PENGELOLA DAN MASYARAKAT DI TAHURA DJUANDA, BANDUNG, JAWA BARAT - Fitriyana, Dian (JURNAL MASTER PARIWISATA; Volume 02, Nomor 02, Januari 2016, 2016)
The Grand Forest Park of Ir. H. Djuanda is a popular ecotourism in Bandung, West Java. The management is conducted by the Management Center helped by the locals. However, it has been disharmonious relationship between the park management and the local community. This article analyses conflict between the management and the community. It discusses causes, implications and solutions to the conflicts. The data were taken from observation, interviews, and documentions which were analysed using qualitative approach. The study shows that the causes of conflict are policy differences, frequent change in management leadership, lack of dissemination of empowerment programs to the people, factors of lower people’s education, and narrow-minded of people’s. The implications are both negative and positive to the empowerment programs.
Keywords: conflict of management; ecotourism; community empowerment; the Djuanda Grand Forest Park